Delaying Wheat Seeding Time and Maize Harvest Improved Water Use Efficiency in a Warm Temperature Continental Monsoon Climate. (1st July 2018) - Xu, Cailong; Zhao, Hongxiang; Zhang, Ping; Wang, Yuanyuan; Huang, Shoubing; Meng, Qingfeng; Wang, Pu
Abstract : Double‐Delay cropping patterns can significantly reduce agricultural water consumption without yield reduction. Annual decreased water content is attributed to the decreased water content in winter wheat season. Late sown winter wheat consumes less water before pre‐winter. Increased maize yield offset reduced wheat yield in appropriate Double‐Delay systems. Appropriate Double‐Delay cropping patterns increase annual profit. This study examined the impact of delaying the sowing time of wheat ( Triticum aestivum L.) and harvesting time of maize ( Zea mays L.) on crop yields in a region with a warm temperature continental monsoon climate. According to farmers' practice (FP), we employed three treatments that each delayed both the maize harvesting and wheat sowing for 10 d, 20 d, and 30 d. No significant differences were observed in annual grain yield among the FP, delayed 10 d (DHS‐10), and delayed 20 d treatments (DHS‐20), while the results for these treatments were significantly higher than those in delayed 30 d treatment (DHS‐30). For all of the treatments, the grain yield of winter wheat decreased with the delay of sowing and the grain yield of summer maize increased with the delay of harvesting. For annual rotation, improved grain yield in maize season compensated for reduced yield in wheat season, for both DHS‐10 and DHS‐20 treatments compared with FP. Total water consumption followed as FP, DHS‐10, DHS‐20, and DHS‐30 order. Total water consumption in DHS‐10 and DHS‐20 treatments decreased by 5.6 and 10.7%, respectively, compared with FP. Higher net economic benefits compared to FP was also obtained in DHS‐10 (+ 495.4 ¥ ha −1 ) and DHS‐20 (+ 877.0 ¥ ha −1 ) treatments. In conclusion, DHS‐20 treatment not only substantially reduced total water consumption, but also maintained stable annual yield and increased profits.